Thermal ablation for benign, non-functioning thyroid nodules: A clinical review focused on outcomes, technical remarks, and comparisons with surgery. (1st October 2020) - Negro, Roberto; Trimboli, Pierpaolo
ABSTRACT: Thermal ablation (TA) is a therapeutic option for benign, non-functioning thyroid nodules causing symptoms of compression and/or aesthetic concerns. TA was initially introduced as a treatment for patients who refused or were ineligible for surgery. In more recent years, the increase in the positive experiences of TA have paved the way for the idea that TA could be suggested as a first-line treatment. The present review was conceived to summarize the evidence achieved in this field, and to offer a clinical perspective on TA, with particular reference to the comparison between TA and surgery. We searched literature that was focused on two types of TA, laser (LA) and radiofrequency (RFA). The searched literature included short- mid-term prospective and retrospective studies, randomized trials, and meta-analyses that demonstrated a satisfactory volume reduction ratio (VRR), and benefits in cosmetic and symptoms scores. An important drawback of the use of TA, is the regrowth of a certain number of nodules, which necessitate further TA procedures or surgery. Long-term randomized controlled trials to evaluate the cost/effectiveness of TA vs surgery are not currently available. The selection of the nodule, the optimization of interventional techniques, and ultimately, a well-timed second treatment, are all factors that should be considered in a proactive strategy to prevent TA failure.